2005
DOI: 10.1128/iai.73.10.6390-6398.2005
|View full text |Cite
|
Sign up to set email alerts
|

Massive Destruction of Malaria-Parasitized Red Blood Cells despite Spleen Closure

Abstract: It is currently accepted that malaria-parasitized red blood cells (pRBC) are eliminated, like senescent erythrocytes, phagocytically by macrophages in the red pulp of the spleen. Here, however, we show that self-healing Plasmodium chabaudi malaria activates spleen closure in C57BL/6 mice. Confocal laser scanning microscopy revealed that spleen closing was manifested by elimination of entry into the red pulp of 3-m polystyrol particles, pRBC, and nonparasitized red blood cells but not of bovine serum albumin. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 35 publications
3
46
0
2
Order By: Relevance
“…1B). Normal splenic structure returned by day 60, when the parasitemia subsided to subpatent levels (2,3,8,29, 54, 67; data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). Normal splenic structure returned by day 60, when the parasitemia subsided to subpatent levels (2,3,8,29, 54, 67; data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, malaria-associated splenomegaly has been associated with increased erythropoiesis in mice (41,52,61,68). Malarial splenomegaly is accompanied by transient alterations in the microarchitecture during acute infection (2,9,29,32,54,65,67), which in mouse infections returns to normal several weeks after the acute parasitemia (1,54,67).…”
mentioning
confidence: 99%
“…A recent study reported loss of MZM, but not MMM, following infection with P. chabaudi. The authors concluded that, as a similar loss occurred following administration of TNF, the MZM loss was the result of up-regulation of TNF in the infected mice (16).…”
mentioning
confidence: 89%
“…We used a nonclonal line of P. chabaudi (59) exhibiting a restriction length polymorphism pattern very similar, but not identical, to that of Plasmodium chabaudi chabaudi AS (28). Erythrocytic stages of P. chabaudi were passaged weekly in NMRI mice.…”
Section: ϫ/ϫmentioning
confidence: 99%
“…The liver plays a central role in malaria: it is the site where the preerythrocytic stages of the malaria parasites have to develop and multiply (in hepatocytes), but it is also the site where the intraerythrocytic stages of the parasites, which are responsible for disease and death, can be trapped and even destroyed (2,3,28). Predominantly the Kupffer cells, which constitute approximately 80 to 90% of total macrophages, contribute to the trapping capacity of the liver.…”
mentioning
confidence: 99%